Earth abundant iron-rich N-doped graphene based spacer and cavity materials for surface plasmon-coupled emission enhancements - Srinivasan, Venkatesh; Vernekar, Dnyanesh; Jaiswal, Garima; Jagadeesan, Dinesh; Ramamurthy, Sai Sathish (ACS Applied Materials & Interfaces, 2016)
We demonstrate for the first time the use of Fe based nanoparticles on N-doped graphene as spacer and cavity materials and study their plasmonic effect on the spontaneous emission of a radiating dipole. Fe-C-MF was produced by pyrolizing FeOOH and melamine formaldehyde precursor on graphene, while Fe-C-PH was produced by pyrolizing the Fe-phenanthroline complex on graphene. The use of the Fe-C-MF composite consisting of Fe-rich crystalline phases supported on N-doped graphene presented a spacer material with 116-fold fluorescence enhancements. On the other hand, the Fe-C-PH/Ag based cavity resulted in an 82-fold enhancement in Surface Plasmon-Coupled Emission (SPCE), with high directionality and polarization of Rhodamine 6G (Rh6G) emission owing to Casimir and Purcell effects. The use of a mobile phone as a cost-effective fluorescence detection device in the present work opens up a flexible perspective for the study of different nanomaterials as tunable substrates in cavity mode and spacer applications.
Keywords: Casimir effect; fluorescence enhancements; iron carbides; N-doped graphene; Purcell factor; surface plasmon-coupled emission

Iron-carbon nanohybrid particles as environmentally benign electrode for supercapacitor - Ratha, Satyajit; Vernekar, Dnyanesh; Sivaneri, Kavin; Jagadeesan, Dinesh; Rout, Chandra Sekhar (Journal of Solid State Electrochemistry, 2017)
In this work, we report the synthesis and electrode applications of iron-carbon nanohybrid particles prepared by carbonization of a nanocomposite of FeOOH nanoneedles and melamine-formaldehyde resin. The chemical composition and microstructure of the material have been characterized using ICP-AES, FT-IR, XRD, FESEM, TEM and XPS. The supercapacitor properties of the MF-Fe-C are studied in detail. A thorough comparison of the supercapacitor performances of MF-Fe-C and bare MF-C has been carried out through detailed electrochemical characterisations employing both two and three-electrode techniques. The nanohybrid showed an enhanced energy density of 127.75 WhKg⁻¹, specific capacitance of ∼408 F g⁻¹ at 1 mVs⁻¹ scan rate, and excellent cyclic stability even after 1000 charge-discharge cycles, making it an intriguing material for high energy density supercapacitor devices.

Efficient bifunctional reactivity of K-doped CrO(OH) nanosheets: exploiting the combined role of Cr(iii) and surface -OH groups in tandem catalysis - Vernekar, Dnyanesh; Ratha, Satyajit; Rode, Chandrashekhar; Jagadeesan, Dinesh (Catalysis Science & Technology, 2019)
This work reports the bifunctional catalytic activity of layered K-doped alpha-CrO(OH). The combined action of the redox active Cr(III) and the surface hydroxyl groups was efficiently used to carry out 2-3 oxidation reactions in tandem followed by condensation/coupling reactions in one pot. Oxidation of benzyl alcohol followed by Knoevenagel condensation or coupling reactions forming C-C and C-N linkages in one pot is demonstrated. The catalyst has been characterized using XRD, IR, TGA, CO2-TPD, cyclic voltammetry, XPS and microscopic techniques to gain insight into the nature of active sites. The role of O- and O2- on the CrO(OH) catalyst in the bifunctional activity was studied using analytical techniques. Recyclability and leaching tests confirmed that K-alpha-CrO(OH) is a stable and environmentally safe catalyst.

Water-promoted surface basicity in FeO(OH) for the synthesis of pseudoionones (PS) and their analogues - Vernekar, Dnyanesh; Sakate, Sachin S.; Rode, Chandrashekhar V.; Jagadeesan, Dinesh (Journal of Catalysis, 2019)
Use of Iron oxyhydroxide (gamma-FeO(OH)) as a robust catalyst for the synthesis of important intermediates like pseudoionones and their analogues through the C-C bond formation reactions like knoevenagel and aldol condensation is explored. These motifs are the building blocks for the construction of the sesquiterpenes as well as the diterpenes such as retinoic acid, Vitamin A etc. Iron oxyhydroxide (gamma-FeO(OH)) was synthesized and well characterized using XRD, FT-IR, TEM, XPS and adsorption studies to establish the catalytic activity. A thorough investigation on the nature of basic sites and the role of water as a promoter was explored based on dye adsorption, in situ methanol dissociation and CO2 adsorption studies. The catalyst also showed a wide range of substrate scope with active methylene groups involving various functional groups such as cyanides, esters and acetophenones along with its stability and reproducibility. (C) 2019 Elsevier Inc. All rights reserved.
Keywords: Bronsted basicity; Iron (III) oxyhydroxide; Knoevenagel condensation; Pseudoionones; Surface hydroxyl groups

Direct oxidation of cyclohexane to adipic acid by a WFeCoO(OH) catalyst: role of bronsted acidity and oxygen vacancies - Vernekar, Dnyanesh; Dayyan, Mohammad; Ratha, Satyajit; Rode, V, Chandrashekhar; Haider, M. Ali; Khan, Tuhin Suvra; Jagadeesan, Dinesh (ACS Catalysis, 2021)
This work reports the catalytic activity of the trimetallic mixed-metal oxyhydroxide WFeCoO(OH) for the direct oxidation of cyclohexane to adipic acid (AA) without the use of concentrated HNO3. WFeCoO(OH) displayed a 40% conversion of cyclohexane and a 67% selectivity to AA under relatively milder conditions of temperature (90 degrees C) and pressure (1 atm). Experimental evidence confirmed the presence of acidic, basic, and redox sites on WFeCoO(OH). The detailed investigation revealed that doping W in the Co-FeO(OH) matrix increased the amount of surface lattice oxygen (OS-L) and caused a significant surge in acidity (5.1 mmol/g). The calculated deprotonation energy of WFeCoO(OH) was 1434 kJ/mol, and the trend in acidity was WCoO(OH) < WFeCoO(OH) < FeCoO(OH) similar to CoO(OH). Energy calculations showed that WFeCoO(OH) had a high propensity to generate oxygen vacancies by the loss of either a water molecule or an oxygen atom (-132.2 or -140.9 kJ/mol, respectively). Basicity was generated due to the presence of conjugate pairs of the surface hydroxyl groups. The combined action of the trifunctional acidic, basic, and redox-active metal centers along with the oxygen vacancies was responsible for the enhanced catalytic performance.
Keywords: Adipic Acid; deprotonation energy; metal oxyhydroxides; multifunctional catalysts; oxygen vacancies